Real estate bubbles and contagion: Evidence from selected European countries - Jean-Louis Bago; Imad Rherrad; Koffi Akakpo; Ernest Ouédraogo (Review of Economic Analysis (REA), 2021)
Using quarterly housing price-to-rent ratios from 1970 to 2020, this paper investigated the presence of real estate bubbles at a national level in six selected European countries, namely France, Germany, Italy, Netherlands, Spain, and the United Kingdom. We applied the generalized sup ADF test developed by Phillips et al. (2015) to detect explosive behavior in house prices. Subsequently, we implemented the non-parametric model with time varying coefficients developed by Greenaway-McGrevy and Phillips (2016) to estimate bubbles contagion among these real estate markets. We found evidence of housing prices exuberance in all these markets. Results suggest that Germany, France, Spain, and the Netherlands experienced a bubble during the COVID-19 pandemic period, pushing prices higher, suggesting that speculators anticipated capital gains. In terms of bubbles migration, we find that bubbles migrate between these real estate markets.
Keywords: C12; G12; R31; 330; Bubble; Contagion; real estate; Europe